Boundary partial regularity for solutions of quasilinear parabolic systems with non smooth in time principal matrix. (June 2015) - Arkhipova, Arina A.; Stará, Jana
Abstract: Partial regularity for solutions of quasilinear parabolic systems with non smooth in time principal matrix in the interior of space–time cylinder Q was proved in Arkhipova et al. (2014). In this paper we extend the results up to the parabolic boundary ∂ p Q . The coefficients of the system are assumed to be only bounded and measurable in the time variable. To prove the result, we apply the method of modified boundary A(t)-caloric approximation.